2021
DOI: 10.3389/fphy.2021.775214
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Antenna Integrated With Solar Cells for WLAN Applications

Abstract: A single-port dual-band antenna integrated with solar cells is reported for the 2.4/5-GHz wireless local area network (WLAN) applications. Thirty solar cells are adopted and integrated into the antenna structure for both energy harvesting and wireless communication. The solar cells can act as a director for the lower band, and the main radiation structure for the higher band. The slot and microstrip antennas are incorporated into the compact structure and multiple resonant modes are utilized for dual-band perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The results of the research showed that the lower band ranges (2.27 GHz -2.5 GHz), while the upper band ranges (4.8 GHz _ 6.9) In future low carbon communication systems. As the paper clarified, the shape of the radiation pattern for the lower band is omnidirectional, which is suitable for the reception process, while the shape of the radiation pattern for the upper band is unidirectional, which is suitable for the transmission process [32]. 16) .…”
Section: Solar Cellbasedmentioning
confidence: 96%
“…The results of the research showed that the lower band ranges (2.27 GHz -2.5 GHz), while the upper band ranges (4.8 GHz _ 6.9) In future low carbon communication systems. As the paper clarified, the shape of the radiation pattern for the lower band is omnidirectional, which is suitable for the reception process, while the shape of the radiation pattern for the upper band is unidirectional, which is suitable for the transmission process [32]. 16) .…”
Section: Solar Cellbasedmentioning
confidence: 96%
“…Coaxial Silicon Nanowire based photovoltaic elements act as efficient power sources for ultra-low power nanoelectronic sensors, and logic gates [8]. SCs are integrated with a single port dual band antenna to serve the twin purpose of wireless communication and energy harvesting for wireless local area network (WLAN) applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…The lower band is 10.4% from 2.37 GHz to 2.63 GHz, while the upper band is 14.3% from 5.52 GHz to 6.37 GHz. A dual-band antenna with a single port was explored in [ 21 ]. It acts as a microstrip antenna at the high-frequency band (4.8–6.9 GHz), while the coupling slot works independently at 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…The above single-port antennas have realized dual-band characteristics with different structures. References [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ] have single-layer designs, but their frequency bands are not wide enough for the mobile communication frequency bands of 33% (0.69–0.96 GHz) and 45% (1.71–2.69 GHz). To extend the bandwidth, multilayer structure designs were employed [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and their impedance bandwidths have expanded significantly.…”
Section: Introductionmentioning
confidence: 99%